Heidi - Ainsworth, Alison; Spyri, Johanna Peluso, Martina (Ladybird London, 2013)
An introduction to the story for younger readers. It has been sensitively abridged and retold to make it suitable for sharing with young children from 5+, whilst retaining all the key parts of the story including Heidi's friendship with Peter, her life in Frankfurt with Clara, and fascinating details about life in the mountains.